Calidad Superficial De Uniones Soldadas Evaluadas Mediante Inspección Visual De Acuerdo Al Código Aws D1.1 - Abanto Rios, Carlos Enrique (2018)
In the present research work, the surface quality of the welded joint was determined by means of a manual electric arc welding process with a coated electrode, with the following characteristics: four T-joints, 6 "x 4" x 2 fillet weld "X 0.25" and a butt joint, slot weld 6 "x 4" x 0.25 " The type and size of discontinuities, fillet weld sizes, groove, size of discontinuities, were determined by the use of various types of weld gauges. Recommended by the American Welding Society. and the evaluation was done with the AWS code D1.1. determining discontinuities of the type: porosity, undercut, lack of filling, overlap, screams, bow stroke, excessive convexity. The results of this descriptive investigation show a great variation in what is apparently a defect, after the evaluation only constitutes a discontinuity, concluding that the type and size of the discontinuity in the specimens of the welded joints vary and are evaluated its possible rejection by constituting a defect with the applicable code.